Hooray for liberty, Charlie Brown! - Stratford, Tracy (Stratford, Tracy. American history., 2016)
When Lucy takes over the Peanuts gang's new tree house and proclaims herself queen, Charlie Brown and their friends are inspired by the Declaration of Independence to stand up to Lucy and declare their freedom.